2018
DOI: 10.1155/2018/8738316
|View full text |Cite
|
Sign up to set email alerts
|

A Multitarget Visual Attention Based Algorithm on Crack Detection of Industrial Explosives

Abstract: This paper is a novel study on crack detection of industrial explosives. The proposed algorithm consists of the following steps:(1) image preprocessing was performed according to the defect features of industrial explosives cartridge, and we developed an improved visual attention based algorithm. This proposed algorithm features a parametric analysis that can be implemented on the image according to the conspicuous maps with the introduction of the concept of defect discrimination ; (2) as compared with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The peak signal-to-noise ratio is a standard for evaluating images, and its value is related to the mean square error of the original image and the result image. In general, the larger the value, the better the processing effect 25 . As shown in Fig.…”
Section: Real-time Detection Methods For Panoramic Multitargetmentioning
confidence: 93%
See 1 more Smart Citation
“…The peak signal-to-noise ratio is a standard for evaluating images, and its value is related to the mean square error of the original image and the result image. In general, the larger the value, the better the processing effect 25 . As shown in Fig.…”
Section: Real-time Detection Methods For Panoramic Multitargetmentioning
confidence: 93%
“…In general, the larger the value, the better the processing effect. 25 As shown in Fig. 4 and Table 1, the peak signal-to-noise ratios of the two result images and the original image are 31.322472 and 31.2947, respectively, and the mean square errors are 45.3321 and 48.2487, respectively.…”
Section: Regularized Filter Recoverymentioning
confidence: 94%
“…The accidental ignition of explosive charges in the launch environment is one of the primary reasons for bore bursts, the mechanism of which has been the focus of considerable research on the launch safety of explosive charges [3,4]. Many scholars [5][6][7][8][9][10] have examined the stress, action time, and hot-spot generation of an explosive charge in the launch environment, finding that factors influencing accidental ignition are the particle size, pores, bottom gaps, cracks, and other defects associated with the explosive charge [11][12][13][14][15]. Wu et al [11] analyzed the influence of particle size on the ignition process and showed that the ignition time increases monotonically with decreasing particle size (50-200 μm).…”
Section: Introductionmentioning
confidence: 99%